LARO (Learners Active Response to Operant) lessons in improving the basic science process skills of elementary pupils - Aureen Kate A. Barantes; Joseline R. Tamoria (University of Muhammadiyah Malang, 2021)
Science is regularly taught in ways that make the data unessential, theoretical, and disengaged from students' experiences. Although most students do anticipate to learn science, they regularly see it as being presented in uninteresting ways. This study aimed to determine the effectiveness of using LARO (Learners Active Response to Operant) lessons in teaching Science and their roles in promoting students' basic science process skills (BSPS). This action research employed a descriptive research design. Thirty Grade IV pupils in a special education-gifted talented (SPED-GT) elementary school in Zambales, Philippines, were selected using convenience sampling. A parallel test was used to determine the level of BSPS before and after the application of LARO lessons. Results revealed that before the utilization of LARO lessons, it was found out that some of the pupils had advance knowledge and they were under the average level of basic science process skills. Throughout the use of educational games, there is an improvement in pupils' performance on their oral participation as recorded in their daily recitation logs. It only shows that the pupils are eagerly motivated. After the use of LARO, pupils improved from average to outstanding level of performance of their BSPS in the post-test. It was revealed by the result of the t-test that LARO lessons were effective in enhancing the basic science process skills of pupils. The researchers recommend the use of LARO lessons as a technique to improve the pupil's BSPS.